Elevating and Recognising Knowledge of Indigenous Peoples to Improve Forest Biosecurity - Kuru, Rose; Marsh, Alby; Ganley, Beccy (Frontiers in Forests and Global Change, 2021)
Current forest biosecurity systems and processes employed in many countries are, in large, constructs of Western principles, values and science knowledge that have been introduced and integrated internationally. They are often devoid of knowledge, and of the values and principles, held by indigenous people, even those who have an intimate and enduring relationship with their forests. Indigenous people are also often overlooked in policy and decision-making processes, yet are often most affected by biosecurity pests and pathogens that impact native plant species that they may rely on for sustenance, cultural or spiritual purposes. By adopting an inclusive approach, scientists and indigenous people can achieve more comprehensive and robust biosecurity outcomes through a shared diversity of knowledge and at the same time serves to elevate and recognise the importance of indigenous knowledge. A co-innovation approach can also result in more widespread adoption of tools or practices by end-users including indigenous people. Understanding New Zealand Māori and their unique knowledge base can help improve forest biosecurity systems and practices, as can discussions of barriers that can and have prevented adoption of inclusiveness. Here we outline key principles behind indigenous engagement, specifically the need to develop enduring relationships.